Investigating the role of parental stress of mothers in predicting academic and social adjustment of students with learning disabilities - Jafary, Zeinab (Social Determinants of Health, 2022)
Background: Parental stress and coping style in the face of life stresses have a long-term effect on the behavior, performance and personality of the child. The aim of this article is to investigate the role of parental stress of mothers in predicting academic and social adjustment of students with learning disabilities. Methods: The present applied research is a descriptive-correlational study. Statistical population of the study included all mothers of children with learning disabilities, received services from government learning disability centers in Mashhad in the winter of 2019 (330 people). Based on the Morgan’s table, 181 people were selected using a convenience sampling method. The Aydin (1983) Parental Stress Scale and the Sinha and Singh Student Adjustment Scale (1993) were used to collect data. Cronbach’s alpha coefficients for all variables and components of the study were greater than 0.7, so the reliability of the research questionnaires is acceptable. Data were analyzed by regression coefficient test using SPSS-22 software. Results: 0.09 of the changes in the level of academic adjustment and 0.06 of the changes in the level of social adjustment of students with learning disabilities were affected by the variable of parental stress of mothers. Conclusion: To improve and enhance the academic and social adjustments of students with learning disabilities, it is necessary to pay attention to mental health, stress status and the styles used by parents, especially mothers, in coping with stressful situations.